2012
DOI: 10.1002/bmc.2727
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of drug delivery after liver chemoembolization: direct tissue doxorubicin measurement by UHPLC‐MS‐MS

Abstract: Because liver cancer is rarely suitable for surgery, transcatheter arterial chemoembolization (TACE) is used for palliative therapy. In this procedure, an emulsion of doxorubicin in iodized oil is injected directly into liver tumors through a catheter positioned within the artery supplying blood flow to the tumor. At present, there is limited understanding of factors affecting the delivery and dispersion of doxorubicin within treated tumors during TACE. This study addresses the development and application of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the present study, we choose DOX as our test drug. According to previous reports (Hong et al, 2006;Baumgarten et al, 2012;Gentil et al, 2014;ElSohly et al, 2015; Gholamrezanezhad et al, 2016;Meng et al, 2016), the dose of DOX used for rabbits ranged from 0.6 to 3 mg/kg; we choose a relatively small dose (1 mg/kg) because of the following two considerations: first, for the detection of DOX in tissues and serum, larger doses of DOX are more suitable. Second, for the safety and welfare of animals, smaller doses of DOX are more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we choose DOX as our test drug. According to previous reports (Hong et al, 2006;Baumgarten et al, 2012;Gentil et al, 2014;ElSohly et al, 2015; Gholamrezanezhad et al, 2016;Meng et al, 2016), the dose of DOX used for rabbits ranged from 0.6 to 3 mg/kg; we choose a relatively small dose (1 mg/kg) because of the following two considerations: first, for the detection of DOX in tissues and serum, larger doses of DOX are more suitable. Second, for the safety and welfare of animals, smaller doses of DOX are more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recent in vivo reports have indicated that the distribution of LIP in the liver tumor tissue does not correlate with that of DOX and accordingly challenges the indirect tumor drug targeting potential of this drug product. 25,26 On the other hand, earlier studies reported higher DOX concentrations in the tumor than in the surrounding liver tissue after administration with LIP. 6,27 In addition, a recent study in our lab indicated an interesting trend for the apparent intracellular availability of DOX to be higher when DOX was emulsified in LIP than when it was administered in a particle based DDS, up to 6 h after dosing.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Several in vitro studies have suggested that lipid excipients in DDSs increase the transport of drugs across biological membranes. A number of hypotheses regarding the mechanisms for this increase have been proposed; these include increased membrane fluidity, inhibition of CM efflux transporters, increased aqueous solubility and/or decreased enzymatic hydrolysis. However, it is difficult to accurately predict the in vivo interactions for locally administered targeted drug products based on in vitro data, since the lack of complex tissue biotransport processes in vitro prolongs contact time between the formulation and the cell model, and thus interaction with the excipients is more likely to occur . Recent in vivo reports have indicated that the distribution of LIP in the liver tumor tissue does not correlate with that of DOX and accordingly challenges the indirect tumor drug targeting potential of this drug product. , On the other hand, earlier studies reported higher DOX concentrations in the tumor than in the surrounding liver tissue after administration with LIP. , In addition, a recent study in our lab indicated an interesting trend for the apparent intracellular availability of DOX to be higher when DOX was emulsified in LIP than when it was administered in a particle based DDS, up to 6 h after dosing . This might be clinically important, as cellular peak concentrations are thought to give a better indication of the antitumor efficacy of DOX than total plasma exposure (AUC) .…”
Section: Introductionmentioning
confidence: 99%
“…The UHPLC-MS/ MS method has been previously described (2). Each analysis was performed in triplicate.…”
Section: Sample Harvest and Analysismentioning
confidence: 99%